73.5k views
4 votes
Use the remainder theorem to find the remainder when f(x) is divided by x-1. Then use the factor theorem to determine whether x-1 is a factor of f(x) f(x)=2x^3-6x^2-3x+13The remainder is __Is x-1 a factor of f(x)2x^3-6x^2-3x+13?

User Zmila
by
6.0k points

1 Answer

1 vote

\begin{gathered} \text{firstly check (x-1) is a factor or remainder .} \\ x-1=0 \\ x=1 \\ f(1)=2-9+13 \\ =6 \\ H\text{ence (x-1) will not the factor of the polynomial , because f(1)}\\e0 \\ \text{thats why 6 will be the remainder of the above polynomial.} \end{gathered}

User Wreck
by
5.8k points